Ethnotaxonomy of buffallo (Bubalus Bubalis) on livestock system of the Gayo Community, Aceh - Nasution, Abdullah Akhyar; Harahap, R. Hamdani; Suyitman, Suyitman; Hijjang, Pawennari (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
This paper aims to reveal the knowledge of the Gayo community about buffalo ethnotaxonomy so as to provide a good alternative for sustainability issues in maintaining local wisdom and identity. This research was conducted in Gayo Lues Regency using a qualitative approach because the main purpose of this study was to explore the knowledge and understanding of the Gayo community based on the emic perspective of the community regarding the classification of buffalo species. The data collection techniques used participatory observation, in-depth interviews, FGDs and document studies. The results showed that the knowledge of the Gayo community regarding the genetic ethnotaxonomy of buffalo can be seen from their ability to classify livestock types based on gender, skin color and horn shape owned by buffalo. There are six types of horns identified, namely: Caweng / Gaweng, Gonok, Gampang, Durung / Cakah, Rukup, Rebah, and Gope / Gupik. As for skin color, there are four categories, namely segem, jeged, impil-impil and sawak. The shape and characteristics possessed are indicators in determining the quality of the buffalo because it is correlated with the ability to endure, have energy and the quality of the meat produced. Knowledge of this matter is very useful for parties with an interest in the world of livestock to be used as a basis for policy making.